Efektivitas Virtual Laboratory Dibandingkan Real Laboratory pada Perkuliahan Hybrid terhadap Kemampuan Berpikir Kritis Mahasiswa - Dewi Nilam Tyas; Barokah Isdaryanti; Feylosofia Putri Agry (Pro-Life, 2023)
Students have the opportunity to carry out Biology practicums through real laboratories in labs and virtual laboratories during post-pandemic hybrid lectures. In this regard, this study aims to compare the effectiveness of real laboratory and virtual laboratory and compare the effectiveness of both through hybrid lectures in improving the critical thinking skills of elementary school teacher education students at Universitas Negeri Semarang. This type of research is a quasi-experimental study with a control group pretest-post-test design. The population in this study were second-semester students taking science laboratory courses, with a sample of 94 students. The research will be carried out at the elementary school teacher education campus, Universitas Negeri Semarang, Central Java in April-June 2022. Biology practicum activities using real laboratories as opposed to using virtual laboratories show that virtual laboratories and real laboratories are effective in improving critical thinking skills. The N-gain score in the virtual laboratory group was 0.4494 (medium) and the N-gain score in the real laboratory group was 0.4867 (moderate). Even though the N-gain is in the moderate category, the score is higher in the real laboratory, so it is concluded that the real laboratory is more effective for increasing critical thinking skills through hybrid lectures.